Analisa Optimalisasi Penerangan Jalan Umum Perkotaan (PJU) di Jalan Sultan Agung Kabupaten Brebes - Sarifudin, Amirun; Diantoro, Wahudin; Tolani, Muhammad (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Public Street Lighting (PJU) is a vital component of urban infrastructure that plays a crucial role in enhancing safety, comfort, and environmental aesthetics. This study aims to analyze the existing condition of public street lighting on Sultan Agung Road based on applicable technical standards, calculate the costs required for repair or replacement, and provide recommendations to improve the effectiveness and efficiency of PJU. The research methods include field observation, interviews with relevant stakeholders, and data analysis based on the standards regulated in the Minister of Public Works Regulation No. 12/PRT/M/2014 concerning Guidelines for Public Street Lighting. The results indicate that the condition of PJU on Sultan Agung Road is still suboptimal, with several issues identified, such as uneven light intensity, broken or non-functioning lamps, and the use of inefficient technology. Based on cost analysis, a specific budget is estimated to be required for the repair and replacement of PJU equipment. Recommended solutions include the use of LED lighting technology, rearrangement of lamp post spacing, and improvement of maintenance systems. This research is expected to serve as a reference for local governments in planning and budgeting for PJU improvements, as well as providing benefits to the community by enhancing comfort and safety on Sultan Agung Road.